Variation of migration behaviour in population - Mika Haapanen (European Regional Science Association (ERSA), 2002)
This paper examines the impact of work status and wages on interregional migration decisions in Finland. Although several studies have controlled for migrant selectivity in the estimation of wages, hardly any have considered the role of work status in the same context. The purpose of this paper is to control for them both in the estimation of selectivity corrected wage equations. In addition, we use the corrected wage predictions as additional determinants when we model the decision of work status. The data is derived from a one-percent random sample from the Finnish Longitudinal Census File. The empirical analysis mainly utilises data from the years 1994 and 1995. The data include information on personal and family status, past labour market record, and regional characteristics of over 60,000 persons. A classification into growth-centre regions and peripheral regions is exploited in the analysis.
Keywords: 330